2022
DOI: 10.1002/ange.202204966
|View full text |Cite|
|
Sign up to set email alerts
|

Controlled Synthesis of Cyclic‐Helical Polymers with Circularly Polarized Luminescence

Abstract: Cyclic polymers attract attention because of their endless structure and unique properties, which differ from the linear analogs. However, the synthesis of cyclic polymers is difficult and prohibits their functions and applications. In this study, we reported chiral cyclic Pd II -catalysts that initiate a living ring-expansion polymerization of isocyanides, yielding a single-handed cyclic-helical poly(phenyl isocyanide), with predictable molecular weight (M n ) and low dispersity (M w /M n ), in good yield. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Experiments have established that the difference in backbone topology results in different molecular properties, e.g., cyclic BBPs exhibit a more compact shape and less interchain association , than their linear analogues. Although experiments , and dissipative particle dynamics simulations have elucidated many macroscopic properties of cyclic BBPs such as viscosity and self-assembled structures, the molecular-level details of structure and dynamics are still missing. Obviously, it would be informative to investigate the similarities and differences in the conformational behavior and properties of cyclic and linear BBPs in order to achieve a fundamental understanding of the chain topology effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have established that the difference in backbone topology results in different molecular properties, e.g., cyclic BBPs exhibit a more compact shape and less interchain association , than their linear analogues. Although experiments , and dissipative particle dynamics simulations have elucidated many macroscopic properties of cyclic BBPs such as viscosity and self-assembled structures, the molecular-level details of structure and dynamics are still missing. Obviously, it would be informative to investigate the similarities and differences in the conformational behavior and properties of cyclic and linear BBPs in order to achieve a fundamental understanding of the chain topology effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cyclic BBPs have emerged as a very interesting material. Experiments have established that the difference in backbone topology results in different molecular properties, e.g., cyclic BBPs exhibit a more compact shape and less interchain association , than their linear analogues. Although experiments , and dissipative particle dynamics simulations have elucidated many macroscopic properties of cyclic BBPs such as viscosity and self-assembled structures, the molecular-level details of structure and dynamics are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…The helix is an essential secondary structure in biomacromolecules and ubiquitous in nature, playing an important role in living systems. Inspired by nature, scientists, especially chemists, have designed and prepared various helical polymers. Among them, helical poly­(phenyl isocyanide)­s (PPIs) exhibit a stable helical structure and have attracted great attention because of their wide applications in chiral separation, chiral recognition, asymmetric catalysis, etc. PPIs are commonly prepared using Ni­(II), Rh­(III), or Pd­(II) complexes. Among them, Pd­(II) complexes are air-stable and highly active. Because the Pd(0)/ t -Bu 3 P system can initiate the polymerization of relevant fluorine monomers to afford Pd­(II)-terminated PF, this Pd­(II)-containing PF could be expected to serve as a catalyst for the polymerization of phenyl isocyanide monomers, rendering functional PF- b -PPI copolymers, exhibiting distinctive optical properties and self-assembly behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Poly­(phenyl isocyanide) (PPI) is a main chain helical polymer that forms a helical structure. , Side chain modification is facile because various reactions can be applied to the phenyl group. , In this regard, studies using PPI derivatives have been reported in the research field of artificial helical polymers. PPI offers a wide range of reaction designs, enabling the creation of a wide range of functional materials. The helical structure provided by PPI can be a label for block copolymers. The introduction of a sufficiently long substituent is a flexible substituent to the PPI π-framework, effectively inducting the liquid crystal nature of PPI. Furthermore, the introduction of chiral units into the side chains can provide chiral monomer precursors.…”
Section: Introductionmentioning
confidence: 99%